1998
DOI: 10.1093/nar/26.2.490
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of the active site tyrosine of vaccinia DNA topoisomerase by glutamate, cysteine or histidine converts the enzyme into a site-specific endonuclease

Abstract: Vaccinia topoisomerase forms a covalent protein-DNA intermediate at 5'-CCCTT downward arrow sites in duplex DNA. The T downward arrow nucleotide is linked via a 3'-phosphodiester bond to Tyr-274 of the enzyme. Here, we report that mutant enzymes containing glutamate, cysteine or histidine in lieu of Tyr-274 catalyze endonucleolytic cleavage of a 60 bp duplex DNA at the CCCTT downward arrow site to yield a 3' phosphate-terminated product. The Cys-274 mutant forms trace levels of a covalent protein-DNA complex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…In DNA topoisomerases, the same active site promotes four phosphoryl transfer reactions: the breakage of internucleotide phosphodiester bonds, the formation of a covalent bond between the active site tyrosine and the cleaved DNA, the cleavage of the tyrosine-DNA complex, and the formation of a new internucleotide bond. Several mutations in the active site can specifically reduce the rate of the later steps without affecting earlier steps (43)(44)(45)(46). Here we provide evidence that poliovirus protein 3AB can tether the soluble polymerase to membranes by direct binding via four residues on the polymerase surface, two of which are part of conserved motif E. Our data do not clarify whether the proteolytic liberation of 3B from 3AB or a larger precursor occurs before or after the protein priming reaction.…”
mentioning
confidence: 56%
“…In DNA topoisomerases, the same active site promotes four phosphoryl transfer reactions: the breakage of internucleotide phosphodiester bonds, the formation of a covalent bond between the active site tyrosine and the cleaved DNA, the cleavage of the tyrosine-DNA complex, and the formation of a new internucleotide bond. Several mutations in the active site can specifically reduce the rate of the later steps without affecting earlier steps (43)(44)(45)(46). Here we provide evidence that poliovirus protein 3AB can tether the soluble polymerase to membranes by direct binding via four residues on the polymerase surface, two of which are part of conserved motif E. Our data do not clarify whether the proteolytic liberation of 3B from 3AB or a larger precursor occurs before or after the protein priming reaction.…”
mentioning
confidence: 56%
“…In addition to its principal activity of DNA relaxation, the reactions catalyzed by the vaccinia topoisomerase I include resolution of Holliday junctions and the production of a 2Ј,3Ј-cyclic phosphate by a mechanism analogous to Flp RNase I (19,35). The topoisomerase can mediate a strand joining reaction in which the 5Ј-hydroxyl end of a DNA chain attacks the cyclic phosphate (36) and can be made to act as an endonuclease by replacing its active site tyrosine with glutamic acid (37). The altered reactivity is reminiscent of the conversion of the endonuclease NaeI into a topoisomerase or of E. coli topoisomerase IV into an endonuclease by single amino acid changes in each instance (38,39).…”
Section: Competition Between the Rna Cleavage Activities Of Flp And Tmentioning
confidence: 99%
“…Catalytic site residues Arg 130 , Lys 167 , and Arg 223 were also substituted with methionine in order to maintain similar hydrophobic contacts along the length of the side chain, while selectively eliminating the charged functional group, a type of substitution not previously studied. The Tyr 274 catalytic tyrosine was substituted with Phe to remove the hydroxyl group that serves as the nucleophile in the transesterification reaction mediating initial cleavage, a type of substitution also studied previously (16,29).…”
Section: Selection Of Amino Acids Formentioning
confidence: 99%
“…Previous studies have shown that the sequence-specific recognition is involved not only in initial DNA binding but in a postbinding conformational step that promotes cleavage (4,6,15). Very extensive mutagenesis of the vaccinia topoisomerase has identified residues involved in catalysis and additional residues important for activation of cleavage after DNA binding (4,6,(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%